Edukacja dla pokoju: odpowiedź na wojnę czy integralny obszar kształcenia człowieka? - Piejka, Agnieszka (Humaniora. Czasopismo Internetowe, 2024)
In this article I justify the need to recognize education for peace as one of the most important permanent areas of human education. Thinking about it should go beyond reacting to the violence and aggression we experience and the pedagogical actions we undertake should be a permanent area of human lifelong education. My argumentation is in the broad understanding of peace, according to which it is a complex and multifaceted process, subject to constant change. I also refer to the premise that peacebuilding is the business and responsibility of all people. All teachers and educators should feel obliged to work in this area, because each of them, can create an educational space for experiencing peace in the individual’s relations with the environment.